2012
DOI: 10.1002/etc.1816
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and prooxidant effects of lanthanum ions on Vicia faba L. seedlings under cadmium stress, suggesting ecological risk

Abstract: The present study combined chemical analyses and biological measurements to investigate biphasic effects of La on Cd stress in leaves of Vicia faba seedlings, which were hydroponically cultivated for 15 d in the combination of 6 µM CdCl(2) and 2 to 480 µM La(NO(3))(3), respectively. The results showed that contents of Cd first elevated above and then declined below the 6 µM single Cd treatment when 2 to 30 µM extraneous La were combined. Contents of mineral nutrients altered differentially and became imbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Indeed, Kawano et al (2002) found that La may trigger oxidative stress in a time- and dose-dependent manner in tobacco ( Nicotiana tabacum ) BY-2 cells, which is a typical effect of REE inducing hormetic dose-responses in plants. Accordingly, Wang et al (2012b) reported that La at low concentrations (i.e., 2–8 μM LaCl 3 ) promoted antioxidation against Cd stress in soybean seedlings, whereas at high concentrations (i.e., 30–480 μM LaCl 3 ) it resulted in prooxidant effects, implying potential ecological risk. Moreover, Fashui et al (2000, 2005) found that increasing the synthesis of ROS decreases the protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Kawano et al (2002) found that La may trigger oxidative stress in a time- and dose-dependent manner in tobacco ( Nicotiana tabacum ) BY-2 cells, which is a typical effect of REE inducing hormetic dose-responses in plants. Accordingly, Wang et al (2012b) reported that La at low concentrations (i.e., 2–8 μM LaCl 3 ) promoted antioxidation against Cd stress in soybean seedlings, whereas at high concentrations (i.e., 30–480 μM LaCl 3 ) it resulted in prooxidant effects, implying potential ecological risk. Moreover, Fashui et al (2000, 2005) found that increasing the synthesis of ROS decreases the protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies that correlate the presence of REE to a higher activity of the antioxidant enzymatic system [112,117,119,130,131,150]. , and 10…”
Section: Enzymatic Systemmentioning
confidence: 99%
“…This survey was further refined by entering the keyword Bpollution^(rare earth elements AND soil AND pollution), leading to a subset of 260 references. Again, the great majority of the references (~57 %) were published in recent years (since 2010), and half of them (130) came from China, Japan, Germany, and France. By replacing the third keyword with Bplant^(rare earth elements AND soil AND plant), we collected 369 references, and when we added pollution to this last refinement (rare earth elements AND soil AND plant AND pollution), we have recovered only 91 references from the previous search, with~57 % published since 2010.…”
Section: Introductionmentioning
confidence: 99%
“…After being taken up by plant roots, Cd could disturb various metabolic processes and physiological activities (e.g., photosynthesis, mineral nutrition, membrane structure, cell respiration, and plant growth) [2,5,6]. Thus, some chemical methods were adopted to alleviate oxidative stress and damage on cultivars exposed to Cd or other heavy metals [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements have been proved to have resistance to heavy metals and thus relieve oxidative damage in plants [1,9]. Previous studies demonstrated that La 3þ at lower concentrations reduced ROS accumulation and promoted antioxidation in V. faba L. seedlings under Cd stress [1,7] and at higher doses inhibited antioxidant enzymes and physiological function in roots and leaves of soybean seedlings [14]. As is well known, Cd can cause reactive oxygen species (ROS) burst, oxidative stress, macromolecule damage, and cell death in plants [12,13].…”
Section: Introductionmentioning
confidence: 99%